PENGARUH PROFITABILITY DAN LEVERAGE TERHADAP CASH HOLDING DENGAN TAX PLANNING SEBAGAI VARIABEL INTERVENING - Mendy Angelia (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2020)
The purpose of this research is to obtain empirical evidence about effect of profitability and leverage to cash holding with tax planning as variable intervening. Population of this research is manufactured companies which listed consistently in Indonesia Stock Exchange during year 2014 until 2017. The sampling technique used was purposive sampling and number of sample used by 162 data. The analysis technique used is multiple regression as the statistic analysis method and path analysis to test the variable intervening. Result of analysis indicate that leverage have negative influence on cash holding while profitability and tax planning have positive influence on cash holding. Leverage have negative influence on cash holding while profitability have positive influence on cash holding. The result from path analysis indicate that profitability don’t have an influence to cash holding with tax planning as variable intervening while leverage have an influence indirectly to cash holding with tax planning as variable intervening.